Mechanisms underlying anticancer effect of lactobacilli (lab 12 and labpc) against human colorectal cancer / Azidah Ali - Ali, Azidah (2015)
Chemotherapy plays a crucial role in treatment of colorectal cancer (CRC). Its effectiveness, however, is often hampered by toxicity-limiting therapeutic effect and drug resistance. Probiotics are thought to be able to prevent CRC through changing of colonic microbiota. This study examined the anticancer of Malaysian LAB and unravel the underlying mechanisms against CRC. Twelve LAB isolated from locally fermented food were screened for anticancer against HCT 116, HT-29 and DLD-1 using MTT assay. CRC cells treated with either LAB strain eliciting the most potent anticancer or Lactobacillus casei strain Shirota (reference strain; LABPC) were subjected to detection of apoptosis by AO/PI staining. The mode of cell death was confirmed by annexin VFITC/ PI. The in vitro findings were validated using a HCT 116 tumour xenograft model (n=6/group). Oral administration (109cfu/ml) of LAB 12 and LABPC, either in freeze dried form (FD) or fermented in soymilk (SM), was performed daily before and after tumour inoculation. Tumours were then excised and homogenized for nitric oxide (NO) production, pro-inflammatory cytokine levels (IL-la, IL-8 and VEGF), antioxidant activity (SOD, CAT and GSH) and caspase-3 activation. The metabolic profiling of serum was also performed using LC/MS Q-TOF and differential expression of the metabolites was established by clustering analysis. Anticancer screening revealed that whilst both HT-29 and DLD-1 remained viable in the presence of all tested LAB, HCT 116 were particularly sensitive to treatment with Lactobacillus plantarum (LAB 12) (IC5o=57.70% ± 39.69) and LABPC (IC50=44.87% ± 18.63) fermented in RPMI. Confocal microscopy of AO/PI stained LAB 12- and LABPC-treated HCT 116 confirmed the presence of apoptotic bodies, chromatin condensation and fragmentation as well as membrane blebbing. Subsequent detection of apoptosis found increased percentage of HCT 116 in early and late apoptotic (indicative of apoptosis) stages following 24, 48 and 72 h treatment with LAB 12 (4.58-46.46%) and LABPC (6.72-51.45%), respectively when compared to untreated HCT 116. In vivo study showed reduction of tumour volume (41%-65%) and weight (22%-46%) in LAB 12- and LABPC-treated mice. Tumour homogenates of LAB 12- and LABPC-treated mice were presented with down-regulation of NO (57%-77%) and pro-inflammatory cytokine [EL-la (34%-71%), IL-8 (15%-67%) and VEGF (18%-64%)] as well as up-regulation of caspase-3 (16%-68%) and antioxidant enzymes [SOD (20%-37%), CAT (37%-46%) and GSH (43%-71%)] levels. Metabolic profiling of serum from LAB 12- and LABPC-treated mice identified significant (p<0.05) up-regulation of nine metabolites associated with antitumour activity and they include eicosapentaenoic acid (5.92-12.14), palmitic acid (8.93-9.12), undecanoic acid (1.46- 5.86), docosapentaenoic acid (3.89-12.64), oleamide (12.52-13.59), dihydroxyvitamin D3 (5.71-6.14), dihydrosphiongosine (13.96-14.09), phytosphingosine (14.99-15.61) and C16 sphinganine (15.99-16.91). The present study reports for the first time that the anticancer effect of LAB 12 and LABPC was mediated through the induction of apoptosis. The apoptotic effect was associated with up-regulation of antioxidant activities and anticancer metabolites levels as well as down-regulation of nitric oxide and pro-inflammatory cytokines. These findings suggest the potential use of Malaysian LAB for prevention of CRC.